Yield and economics of pigeonpea as influenced by different intercropping systems and weed management practices - Sunil Kumar Singh; H. S. Kushwaha (Annals of Agricultural Research, 2023)
The field experiment was conducted on sandy loam soil at Agriculture Farm of Mahatma Gandhi Chitrakoot Gramodaya Vishwavidyalaya, Chitrakoot, Satna (M.P.) during the kharif 2016 and 2017 to evaluate productivity and profitability of pigeonpea under intercropping systems and weed management practices. Seed and stover yield and harvest index were recorded significantly higher under pigeonpea sole (10.83 q/ha, 26.94 q/ha and 28.67%) followed by pigeonpea + greengram (2:2) intercropping system (10.15 q/ha, 25.33 q/ ha and 28.61%). In weed control methods, seed yield of pigeonpea was obtained significantly superior under pendimethalin 30% + imazethapyr 2% @ 1kg/ha (12.43 q/ha) and Imazamox 35% + imazethapyr 35% @ 30 g/ha (12.38 q/ha) while, stover yield was observed significantly greater under Imazamox 35% a.e.+ imazethapyr 35% @ 30 g/ha (32.03 q/ha) followed by pendimethalin 30% + imazethapyr 2% (30.05 q/ha) . The gross and net monetary returns and benefit-cost ratio were recorded significantly higher under pigeonpea + greengram (2:2) intercropping system (`64251, 39616 and 2.60). However in weed control methods, significantly maximum gross and net monetary returns was estimated under pendimethalin 30%+ imazethapyr 2% @ 1kg/ha (`68947, 43086) followed by Imazamox 35% + imazethapyr 35% @ 30 g/ha (`67984, 41669). The maximum benefit - cost ratio was obtained with the treatment having pendimethalin 30%+ imazethapyr 2% @ 1kg/ha (2.67).